An Observational Based Modeling of the Surface Layer Particulate Nitrate in the North China Plain During Summertime. Issue 18 (13th September 2021) - Tan, Zhaofeng; Wang, Haichao; Lu, Keding; Dong, Huabin; Liu, Yuhan; Zeng, Limin; Hu, Min; Zhang, Yuanhang
Abstract: Particulate nitrate (pNO3 − ) is an important component in atmospheric fine particulate matter. Here, we present a case study investigating the production and loss processes of pNO3 − in surface‐layer based on the observation at a regional site Wangdu in North China Plain (NCP) during summer. The averaged diurnal of nitric acid (HNO3 ) production reached a maximum of 1.5 μg m −3 h −1 determined from the observed OH and NO2, indicating a fast HNO3 production in the surface layer during the daytime. The chemical processes affecting surface nitrate concentration and daily variation were simulated by a box model based on the Regional Atmospheric Chemical Mechanism version 2 and coupled with the ISORROPIA‐II thermodynamic equilibrium model. The chemical formation of total soluble nitrate (TNO3 ) at the surface layer cannot explain the fast increase of pNO3 − in the morning and overshoot pNO3 − in the afternoon, suggesting missing processes in the model. The pNO3 − budget analysis suggests the importance of entrainment from residual layer air into the surface layer as an important process for surface pNO3 − concentration enhancement in the early morning. In the afternoon, the partition to pNO3 − was limited due to the high temperature near the ground. Nevertheless, the observed fast nitrate production still significantly overshot pNO3 − in the afternoon. This difference indicates HNO3 production was less efficient throughout the boundary layer than what was observed in the surface layer. Our results highlight the importance of vertical measurements to understand the formation mechanism of nitrate pollution in summer. Plain Language Summary: We present a case study investigating the production and loss processes of particulate nitrate (pNO3 − ) on the ground‐based on the observation at a regional site Wangdu in North China Plain during summer. We observed a fast nitrate production in the surface layer during the daytime. By using a model simulation, we found the chemical formation at the surface layer cannot explain the fast increase of pNO3 − in the morning and rapidly decline in the afternoon, suggesting missing processes in the model. Model result suggests the entrainment from upper air into the surface layer is an important source for surface pNO3 − in the early morning. In the afternoon, high temperature limits the produced gas phase nitrate transfer to particle phase. Nevertheless, the observed fast nitrate production from gas phase reaction still significantly overshot pNO3 − in the afternoon. This difference suggests the nitrate production was less efficient throughout the sky than what was observed on the ground. Our results highlight the importance of vertical measurements to understand the formation mechanism of nitrate pollution in summer. Key Points: The chemical formation of particulate nitrate (pNO3 − ) at the surface layer cannot explain the daytime variation of pNO3 − The residual layer entrainment is an important process for surface pNO3 − enhancement in the early morning HNO3 production is less efficient throughout the boundary layer than what is observed in the surface layer in the afternoon